The psychometric properties of the 'Hospital Survey on Patient Safety Culture' in Dutch hospitals - Wagner Cordula; Christiaans-Dingelhoff Ingrid; Smits Marleen; Wal Gerrit; Groenewegen Peter P (BMC, 2008)
Abstract Background In many different countries the Hospital Survey on Patient Safety Culture (HSOPS) is used to assess the safety culture in hospitals. Accordingly, the questionnaire has been translated into Dutch for application in the Netherlands. The aim of this study was to examine the underlying dimensions and psychometric properties of the questionnaire in Dutch hospital settings, and to compare these results with the original questionnaire used in USA hospital settings. Methods The HSOPS was completed by 583 staff members of four general hospitals, three teaching hospitals, and one university hospital in the Netherlands. Confirmatory factor analyses were performed to examine the applicability of the factor structure of the American questionnaire to the Dutch data. Explorative factor analyses were performed to examine whether another composition of items and factors would fit the data better. Supplementary psychometric analyses were performed, including internal consistency and construct validity. Results The confirmatory factor analyses were based on the 12-factor model of the original questionnaire and resulted in a few low reliability scores. 11 Factors were drawn with explorative factor analyses, with acceptable reliability scores and a good construct validity. Two items were removed from the questionnaire. The composition of the factors was very similar to that of the original questionnaire. A few items moved to another factor and two factors turned out to combine into a six-item dimension. All other dimensions consisted of two to five items. Conclusion The Dutch translation of the HSOPS consists of 11 factors with acceptable reliability and good construct validity. and is similar to the original HSOPS factor structure.